Precision scalpels for the epigenome: next-gen editing tools in targeted therapies - Zhang, Ruiming; Yao, Tianqi; Fan, Meiyin; Jiang, Xiaoying; Wang, Keshan; Cui, Min; Bing, Kaijian; Xia, Xiaotian (Frontiers in Medicine, 2025)
This article reviews the fundamental concepts of epigenetics and its related mechanisms, and discusses recent advances in epigenetic gene editors and their applications in disease treatment. First, the article introduces the concept of epigenetic inheritance and the four main epigenetic mechanisms. Then, after briefly outlining traditional gene editing, it presents epigenetic gene editors, their associated tools, and the historical context of their development. Subsequently, the article describes the working principles and advantages of epigenetic editing tools such as KRAB and DNMT. Addressing the current bottlenecks in the field, the article provides an in-depth analysis of editing efficiency and specificity, long-term safety, and the complexity of clinical applications. In addition, it discusses optimization strategies for delivery systems, minimization of off-target effects, and therapeutic approaches for multigene disorders. Finally, the article outlines the progress of epigenetic editors in both neoplastic and non-neoplastic disease research. In summary, this article offers a comprehensive review of the theoretical foundations of epigenetics, the evolution of gene editing tools, and the latest advances in epigenetic editors for disease treatment, providing a valuable reference for future research and clinical application.